2014
DOI: 10.1167/iovs.14-14453
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression ofHtrA1and Exposure to Mainstream Cigarette Smoke Leads to Choroidal Neovascularization and Subretinal Deposits in Aged Mice

Abstract: The HtrA1 overexpression and mainstream cigarette smoke can independently lead to CNV. The HtrA1 gene is a strong risk factor for wet AMD, but not all of the HtrA1 Tg mice developed CNV, suggesting that CNV development depends on multiple risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 52 publications
4
33
1
Order By: Relevance
“…Vierkotten et al (17) also observed fragmentation of the elastic layer in Bruch's membrane, and Jones et al (16) reported branching of choroidal vessels, polypoidal lesions, and severe degeneration of the elastic lamina or tunica media of choroidal vessels in the same model. When HtrA1 expression was driven by the CAG promoter in a transgenic mouse model, an even more severe phenotype was induced compared with previous reports of AMD patient-like choroidal neovascularization (23). These results indicate that overexpression of HtrA1 alone can evoke choroidal vasculopathy or neovascularization, and they also provide supporting evidence for the association of the insertion/deletion variant of HTRA1 regulatory element with wet AMD (7,8).…”
Section: Characterization Of Htra1 Regulatory Elementssupporting
confidence: 66%
See 2 more Smart Citations
“…Vierkotten et al (17) also observed fragmentation of the elastic layer in Bruch's membrane, and Jones et al (16) reported branching of choroidal vessels, polypoidal lesions, and severe degeneration of the elastic lamina or tunica media of choroidal vessels in the same model. When HtrA1 expression was driven by the CAG promoter in a transgenic mouse model, an even more severe phenotype was induced compared with previous reports of AMD patient-like choroidal neovascularization (23). These results indicate that overexpression of HtrA1 alone can evoke choroidal vasculopathy or neovascularization, and they also provide supporting evidence for the association of the insertion/deletion variant of HTRA1 regulatory element with wet AMD (7,8).…”
Section: Characterization Of Htra1 Regulatory Elementssupporting
confidence: 66%
“…Thus, HTRA1 may play an important role in cell growth and differentiation, tissue and/or organ formation, and the onset of disorders. Correspondingly, a transgenic mouse with expression of mouse HtrA1 driven by a chicken actin (CAG) promoter was used to establish a model for choroidal neovascularization, and this model exhibited a significant reduction in tolerance to smoking (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking has a significant impact on both RPE cells and photoreceptors [32,33]. One example is that smoking leads to abnormal deposits in the RPE cells and disorganizes photoreceptors anatomically [33].…”
Section: Discussionmentioning
confidence: 99%
“…One example is that smoking leads to abnormal deposits in the RPE cells and disorganizes photoreceptors anatomically [33]. These aspects remain incompletely understood; however, two important functional pathways provide an important theoretical framework.…”
Section: Discussionmentioning
confidence: 99%